Self-editing: how the writing process shapes the writer-self - Perdue, Brandon (My University, 2008)
Paper presented at the 2008 Nature, Art, Self Conference by Brandon Perdue (University of Mary Washington, VA) in which he describes how the writing process shapes the identity which creates the text (the writer-self).
6 p.
Keywords: Composition; Authorship; Author; Writer; Writer-self; Writing process; Writing; Creative writing